Sistem Pendukung Keputusan Penerimaan Calon Guru Honor Di Smk Gotong Royong Gorontalo Menggunakan Metode Topsis - M Salim (Universitas PGRI Semarang, 2018)
Abstract - The main figure is most important in all schools is the teacher. School quality can be measured through the output generated is not only measured by the status of the school, a large number of students and the magnificent building with complete facilities in it. Output or a good and qualified graduates, supported by qualified teachers, and vice versa. On the initial observations conducted on SMK Gotong Royong Gorontalo found the problem process was based on Nepotism without regard to the quality of the candidate, the assessment and test results using the manual way, the accumulation of files applicants, delays decision-making and mistakes administering the value because the human factor error. The purpose of this research is to produce decision support system applications to process data is the acceptance of honorary teacher at SMK Gotong Royong Gorontalo and be known how the application of TOPSIS method in the process is Honorary teacher acceptance so that the process of assessment is better. The results showed a decision support system provides simplicity in the process of determining prospective teachers respect by applying discusses decision support system that is computer-based, so that the process is faster and the test results test try the White box testing can be inferred that the flowchart menu, the application of the Test the test case with white box testing approach can produce the systems and processes on a looping flowchart in the system to be effective and efficient. Keyword : decision support systems, teacher honorarium, TOPSIS